Importance of communication in determining retailer-supplier relationship quality: a relationship marketing approach - Aziz, Md. Tareque (© 2012 ELK's International Journal of Marketing, 2016)
This article was published in ELK ASIA PACIFIC JOURNAL OF MARKETING AND RETAIL MANAGEMENT [© 2012 ELK's International Journal of Marketing] and the definite version is available at : http://www.elkjournals.com/journalcurrentissue.asp?JType=EAPJMRM&VType=3&IType=1 The article website is at: http://www.elkjournals.com/